GOTILON FEAST AND SOCIAL IDENTITY: ACTUALIZATION AND INCULTURATION AT THE ONAN BARU RESORTS CHURCH, SAMOSIR, NORTH SUMATERA - Silaban, Priska Natalia; Simbolon, Elvri Teresia; Firmando, Harisan Boni; Simbolon, Rusmauli; Lumbantobing, Roida (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This research aims to examine how social identity is actualized during the Gotilon Feast at the HKBP Onan Baru Resort Church in Samosir Regency, North Sumatera. Gotilon Feast is understood as a space of inculturation that combines Batak Toba culture and Christian values, serving as a medium of expressing the cultural, personal, and communal identity of the Batak Toba-Protestant Christian congregation. The research employs a qualitative-descriptive approach, collecting data through interviews, and documentation, analyzed using social identity theory, Pierre Bourdieu's habitus theory, and Habermas's public sphere. The results show that the celebration reflects strong symbolic practices such as the use of ulos, tortor, Batak music (gondang), and the giving of silua. In addition to being a Thanksgiving ritual, the celebration also reveals social dynamics, including a shift in meaning toward a symbol of prestige and social status. The study also found generational differences in perception and variation in practice between rural and urban churches. Through the lenses of social identity theory, Pierre Bourdieu's concept of habitus, and Habermas' public sphere theory, the Gotilon Festival is seen as a cultural-religious event that constructs social identity through the intersection of faith and tradition. Thus, the celebration serves as both a religious practice and a public space where cultural and spiritual negotiations occur.